2011
DOI: 10.1089/hum.2010.083
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein FacilitatesIn VivoDelivery of α-Tocopherol–Conjugated Short-Interfering RNA to the Brain

Abstract: We originally reported the use of vitamin E (a-tocopherol) as an in vivo vector of short-interfering RNA (siRNA) to the liver. Here, we apply our strategy to the brain. By combining high-density lipoprotein (HDL) as a second carrier with a-tocopherol-conjugated siRNA (Toc-siRNA) in the brain, we achieved dramatic improvement of siRNA delivery to neurons. After direct intracerebroventricular (ICV) infusion of Toc-siRNA/HDL for 7 days, extensive and specific knock-down of a target gene, b-site amyloid precursor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…16,17 However, in our system, no gene expression was detected in neuronal cells. This discrepancy can be explained by differences in the cargo.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…16,17 However, in our system, no gene expression was detected in neuronal cells. This discrepancy can be explained by differences in the cargo.…”
mentioning
confidence: 56%
“…16 In parallel with enhanced cellular uptake ( Figure 1B), the gene silencing effects increased with increasing ApoE concentration ( Figure 1C).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…We reported efficient siRNA delivery by ICV administration when using lipoprotein as an in vivo carrier for the siRNA [13]. We used a-tocopherol-conjugated siRNA to bind serum HDL, and we achieved dramatic improvement in siRNA delivery to neurons.…”
Section: Intracerebroventricular Administrationmentioning
confidence: 99%
“…Serum HDL and HDL-like particles have similar particle size and density and both use apolipoprotein E as a ligand for receptors. The dose of unconjugated siRNA needed for target suppression was as much as 3 µmol [9], whereas we found that only 3 nmol of a-tocopherol-conjugated siRNA with HDL could inhibit a target gene to a comparable degree [13].…”
Section: Intracerebroventricular Administrationmentioning
confidence: 99%